2019
DOI: 10.3390/cells8121530
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Cardiovascular Medicine: Historical Overview and Future Prospects

Abstract: Cardiovascular diseases remain the leading cause of death in the developed world, accounting for more than 30% of all deaths. In a large proportion of these patients, acute myocardial infarction is usually the first manifestation, which might further progress to heart failure. In addition, the human heart displays a low regenerative capacity, leading to a loss of cardiomyocytes and persistent tissue scaring, which entails a morbid pathologic sequela. Novel therapeutic approaches are urgently needed. Stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 226 publications
(254 reference statements)
0
25
0
Order By: Relevance
“…Embryonic stem cells (ESCs) are pluripotent cells derived from the inner cell mass of pre-implantation blastocysts of a murine or human host. ESCs showed the ability to discriminate in cells of all three germ layers, thus, including the generation of cardiac myocytes [ 40 , 72 , 73 ]. From early studies conducted on different animal models of acute MI and IHDs, such as pig or guinea pig, the injected ESCs have shown the ability to act as a biological pacemaker in electro-physiologically silenced or atrioventricular blocked hearts [ 74 , 75 ].…”
Section: Cardiac Regeneration and Stem Cells Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Embryonic stem cells (ESCs) are pluripotent cells derived from the inner cell mass of pre-implantation blastocysts of a murine or human host. ESCs showed the ability to discriminate in cells of all three germ layers, thus, including the generation of cardiac myocytes [ 40 , 72 , 73 ]. From early studies conducted on different animal models of acute MI and IHDs, such as pig or guinea pig, the injected ESCs have shown the ability to act as a biological pacemaker in electro-physiologically silenced or atrioventricular blocked hearts [ 74 , 75 ].…”
Section: Cardiac Regeneration and Stem Cells Therapymentioning
confidence: 99%
“…For this reason, many countries have imposed prohibitions on research funding and on the use of human ESCs (hESCs) derived from an embryo destruction [ 18 ]. In addition, some studies have identified the ability of ESCs to generate teratomas (tumors of mixed germ layers) and graft refusal when transplanted undifferentiated [ 73 ], together with genetic variability and the risk of immune rejection due to their nature of pluripotency and allogeneic cell type [ 83 ]. Many efforts to enhance purifications and differentiations protocols are ongoing [ 84 ].…”
Section: Cardiac Regeneration and Stem Cells Therapymentioning
confidence: 99%
“…Obtained easily, these cells can differentiate into any desired cells theoretically, and are applied to the study of any target cells, which are not affected by species-specific differences. The iPSCs disease models have been applied to some organ systems [21][22][23][26][27][28][29][30][31][32]. Besides, the current reprogrammed iPSCs have been widely used to study disease models and cell replacement therapy in animal experiments, which is possible to study the pathogenesis of diseases [33].…”
Section: Ivyspringmentioning
confidence: 99%
“…Particularly, human ESCs in a cocktail of factors targeting potential death pathways showed improved survival [ 129 ]. It was demonstrated that one-to-one electrophysiological coupling between the graft and host cardiac cells enhanced the engraftment of human ESC-derived CMs and suppressed ventricular arrhythmia [ 130 ]. Moreover, Shiba and colleagues reported reduced immunogenicity in the MHC-matched Cynomolgus monkeys upon the allogenic transplantation of iPSC-CMs [ 131 ].…”
Section: Genetically Modified Stem Cell For MI Treatmentmentioning
confidence: 99%